Representation of Social Identity in Contemporary Prose: A Study of Literary Works that Depict Class Conflict - Fatimah, Ade Fitria (Journal of Literary Prose and Society, 2024)
This study explores the representation of social identity and class conflict in contemporary prose, focusing on how literary works reflect and critique societal structures and inequalities. Through a close examination of selected novels and short stories, this research investigates the nuanced portrayal of class-based struggles and the ways in which characters navigate their identities within stratified social settings. By analyzing narrative techniques, character development, and thematic elements, the study seeks to understand how contemporary prose serves as a vehicle for both personal and collective resistance against class-based oppression. The research underscores the role of literature as a mirror of societal dynamics, revealing how authors employ literary devices to expose the complexities and challenges faced by individuals in different socioeconomic contexts. The findings aim to contribute to a deeper understanding of the intersection between literature and society, highlighting the power of prose to foster awareness and empathy regarding social inequality. This study ultimately positions contemporary prose as a critical space for examining, challenging, and reflecting on the realities of social identity and class conflict in modern society.